The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.24256/itj.v4i1.2537
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Resilience in Facing Changes in Education Policy due to Covid-19 Pandemic

Abstract: This is a descriptive study aiming at investigating resilience among university teachers, especially in dealing with changes in education policies during the covid-19 pandemic. The participants of this research were lecturers at the English education study program at a state university in West Nusa Tenggara Province. The data were obtained through an online questionnaire which was distributed to all potential respondents. Among 39 teaching staff, 26 of them completed and returned the form. Based on the data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Indonesian context, a study by Amin et al (2022) found that 86.4% teachers in Indonesia have high and very high resilience in facing education policy changes due to Covid-19 pandemic. The teacher participants in this study are also aware that changes in education policy is something inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesian context, a study by Amin et al (2022) found that 86.4% teachers in Indonesia have high and very high resilience in facing education policy changes due to Covid-19 pandemic. The teacher participants in this study are also aware that changes in education policy is something inevitable.…”
Section: Introductionmentioning
confidence: 99%